Passive Smokers Pregnant Women with Low Birth Weight - Sofia Mawaddah; Sulis Tiyawati (JURNAL INFO KESEHATAN, 2021)
The number of cases of low-birth-weight babies at dr. Doris Sylvanus Regional General Hospital, Palangka Raya in 2017 was as many as 378 cases. One of the causes of low birth weight was mothers who smoke actively or passively during pregnancy. The objective of this study is to determine the relationship between passive smoking pregnant women and the incidence of low birth weight at the dr. Doris Sylvanus Regional General Hospital, Palangka Raya. This research is an observational study using a cross-sectional research design and a retrospective approach with a sample of 45 mothers obtained using purposive sampling technique. Data analysis used Chi-Square statistical test. The results of the study found that pregnant women with heavy passive smokers gave birth to babies with low birth weight as many as 28 people (62.2%) and 1 person who did not have low birth weight babies (2.2%). Meanwhile, pregnant women with light passive smokers who gave birth to low birth weight were 12 people (26.7%) and 4 people did not have low birth weight (8.9%). Thus, there is a significant relationship between passive smoking pregnant women and the incidence of low birth weight at dr. Doris Sylvanus Regional General Hospital, Palangka Raya with p = 0.047, OR = 9.33. For further researchers, it is recommended to examine the factors that cause pregnant women to smoke passively with the incidence of low-birth-weight babies.